Quality Improvement Initiatives: The Missed Opportunity for Health Plans - Fernandez-Lopez, Sara (Engage Healthcare Communications, LLC, 2009)
BACKGROUND: The increase in healthcare cost without direct improvements in health outcomes, coupled with a desire to expand access to the large uninsured population, has underscored the importance of quality initiatives and organizations that provide more affordable healthcare by maximizing value. OBJECTIVES: To determine the knowledge of managed care organizations about quality organizations and initiatives and to identify potential opportunities in which pharmaceutical companies could collaborate with health plans in the development and implementation of quality initiatives. METHODS: We conducted a survey of 36 pharmacy directors and 15 medical directors of different plans during a Managed Care Network meeting in 2008. The represented plans cover almost 74 million lives in commercial, Medicare, and Medicaid programs, or a combination of them. RESULTS: The responses show limited knowledge among pharmacy and medical directors about current quality organizations and initiatives, except for quality organizations that provide health plan quality accreditation. The results also reveal an opportunity for pharmaceutical companies to collaborate with private health plans in the development of quality initiatives, especially those related to drug utilization, such as patient adherence and education and correct drug utilization. CONCLUSION: Our survey shows clearly that today's focus for managed care organizations is mostly limited to the organizations that provide health plan quality accreditation, with less focus on other organizations.